PENGEMBANGAN MATHEMATICS MOBILE LEARNING APPLICATION (MMLA)-SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) UNTUK SISWA KELAS 8 SEBAGAI SUMBER PEMBELAJARAN MANDIRI BERBASIS ANDROID - Zefriyenni Zefriyenni; Hayatul Mardhiyah (Jurnal Teknologi Informasi dan Pendidikan, 2017)
In the education required changes in the application of the development of teaching and learning methods to improve student interest in learning mathematics, especially in doing mathematics problems class VIII about the system of linear equations two variables. The low ability of students in the learning process and workmanship problems caused by various factors, such as learning systems used are still conventional. Therefore, the author helps SMP N 1 Pariangan to transform the learning resources of the book into digital form in accordance with the development of mobile device technology today, by making a mobile learning application. Mobile learning application displays about two-variable linear equation system, displaying learning materials , news menu, and task upload system. The application is made in the form of mobile application for android based mobile devices. With this mobile learning application can improve the ability, and facilitate students in learning mathematics about the system of linear equations two variables. Keywords: Android Internet, Mobile Application, Mobile Learning, Spldv